2018
DOI: 10.1111/ddi.12735
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting responses in community structure and phenology of migratory and non‐migratory pollinators to urbanization

Abstract: Aim Anthropogenic landscape change, such as urbanization, can affect community structure and ecological interactions. Furthermore, changes in ambient temperature and resource availability due to urbanization may affect migratory and non‐migratory species differently. However, the response of migratory species to urbanization is poorly investigated, and knowledge for invertebrates in particular is lacking. Our aim was to investigate whether there was a shift in community structure and phenology of hoverflies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…Within West African countries urban growth and agricultural intensification can trigger changes in biodiversity leading to either a homogenization or a reduction of important insect communities affecting the ecosystem service of pollination [35][36][37][38][39]. The fact that urban farming households in Ouagadougou were highly specialized in the cultivation and marketing of crops which often rely substantially upon insect pollination and from which they earn most of their total household income, made these households vulnerable to loss of pollination services by insects.…”
Section: Discussionmentioning
confidence: 99%
“…Within West African countries urban growth and agricultural intensification can trigger changes in biodiversity leading to either a homogenization or a reduction of important insect communities affecting the ecosystem service of pollination [35][36][37][38][39]. The fact that urban farming households in Ouagadougou were highly specialized in the cultivation and marketing of crops which often rely substantially upon insect pollination and from which they earn most of their total household income, made these households vulnerable to loss of pollination services by insects.…”
Section: Discussionmentioning
confidence: 99%
“…Urbanization can also increase the propensity for residency or overwintering through the provision of winter refugia or foraging resources, such as garden flowers. Luder et al (2018) demonstrated that migratory hoverflies appeared earlier in the season in urban areas compared to agricultural areas, indicating that cities may provide favorable conditions for overwintering. Warming temperatures have also led to an increase in overwintering of migratory species in the UK, such as the red admiral butterfly (Vanessa atalanta), although much of the population still immigrates to the UK each spring (Sparks et al, 2005;Fox and Dennis, 2010).…”
Section: Future Directions and Gaps In Knowledgementioning
confidence: 99%
“…, Luder et al. ). Similarly, in arid regions, management of urban flora can extend plant bloom, with benefits to pollinators (Neil et al.…”
Section: Introductionmentioning
confidence: 98%